KAJIAN BUDAYA JEPANG PADA PROSES DAN TEKNIK SENI LUKIS TAKASHI MURAKAMI - Dwi Yunizal (Gorga : Jurnal Seni Rupa, 2022)
Contemporary artist Takashi Murakami from Japan works in painting, sculpture, and commercial media including fashion, merchandise and animation with the superflat theory. The creative process combines traditional culture with contemporary culture, this study aims to understand Murakami's background in managing the dynamics of traditional culture with critical and genius visual discourse. The superflat theory was finally able to lead Murakami to become a well-known artist, due to the meeting of the dynamics of traditional and capitalist culture in the global market. The use of kawaii elements which mean cute and sweet, both as a style and a way of life can be found in Murakami's art. Symbolism plays an important role in attracting people's attention and working to elevate otaku culture's status as a representation of Japan. Murakami's mythical sensibility presents traditional Japanese, Chinese, and Buddhist myths giving mythopoeic achievements. This study uses library research with a semi-systematic approach that originates from journals, dissertations, theses, and internet media, based on the results of data and information processing, the works of artist Murakami are influenced by Japanese cultural structures such as Soga Shohaku, kawaii, and otaku. Murakami's awareness in understanding art discourse by incorporating a kawaii style, so that it is easily accepted in the global art market. Understanding how Murakami's formula manages traditional culture to become today's art, can be analyzed in a work entitled “Dragon in Clouds – Indigo Blue”. The conclusion of Murakami's work is the symbolism influenced by his personal experience.Keywords: soga shohaku, kawaii, otaku, superflat. AbstrakSeniman kontemporer Takashi Murakami dari Jepang mengerjakan karya lukisan, patung, dan media komersial termasuk fashion, barang dagang, dan animasi dengan teori superflat. Proses kreatif memadukan budaya tradisional dengan budaya kontemporer. Penelitian ini bertujuan memahami latar belakang Murakami mengelola dinamika budaya tradisional dengan wacana visual yang kritis dan jenius. Teori superflat akhirnya mampu mengantarkan Murakami menjadi seniman ternama, karena pertemuan dinamika budaya tradisional dan kapitalis di pasar global. Penggunaan unsur kawaii yang berarti imut dan manis, baik sebagai gaya maupun gaya hidup dapat ditemukan dalam karya seni Murakami. Simbolisme memainkan peran penting untuk menarik perhatian orang, dan berupaya mengangkat status budaya otaku sebagai representasi Jepang. Kepekaan mitis Murakami menghadirkan mitos tradisional Jepang, Cina, dan Buddha memberikan pencapaian mythopoeic. Penelitian ini menggunakan penelitian kepustakaan dengan pendekatan semi-sistematik yang bersumber dari jurnal, disertasi, tesis, dan media internet. Berdasarkan hasil pengolahan data dan informasi, karya seniman Murakami dipengaruhi oleh struktur budaya Jepang seperti soga shohaku, kawaii, dan otaku. Kesadaran Murakami dalam memahami wacana seni dengan memasukkan gaya kawaii, sehingga mudah diterima di pasar seni global. Memahami bagaimana formula Murakami mengelola budaya tradisional menjadi seni masa kini, dapat dianalisis dalam karya berjudul “Dragon in Clouds – Indigo Blue”. Kesimpulan dari karya Murakami adalah simbolisme yang dipengaruhi pengalaman pribadinya.Kata Kunci: soga shohaku, kawaii, otaku, superflat. Author:Dwi Yunizal : Institut Seni Indonesia Yogyakarta References:Birlea, O. M. (2021). “Cute Studies”. Kawaii (“Cuteness”) – A New Research Field. Philobiblon, 26(1), 83–100. https://doi.org/10.26424/philobib.2021.26.1.05.Borggreen, G. (2011). Cute and Cool in Contemporary Japanese Visual Arts. The Copenhagen Journal of Asian Studies, 29(01), 39–60. https://doi.org/10.22439/cjas.v29i1.4020.Hashimoto, M. (2007). Visual Kei Otaku Identity - An Intercultural Analysis. Intercultural Communication Studies, XVI(1), 87–99. https://www.researchgate.net/publication/239576790_Visual_Kei_Otaku_Identity-An_Intercultural_Analysis.Hu, X. (2021). Is Takashi Murakami’s Art an Exploration of Symbolism ?. Proceedings of the 2021 6th International Conference on Modern Management and Education Technology,  582, 560–564. https://doi.org/10.2991/assehr.k.211011.101.Khairi, I. A ., & Hafiz, H. (2022). Kajian Estetika Lukisan Realis Kontemporer Drs. Irwan, M.Sn. yang Berjudul di Ujung Tanduk. Gorga: Jurnal Seni Rupa, 11(01), 138-146. https://doi.org/10.24114/gr.v11i1.34129.    Mamat, R., Rashid, R. A., Paee, R., & Ahmad, N. (2022). VTubers and anime culture: A case study of Japanese learners in two public universities in Malaysia. International Journal of Health Sciences, 6(S2), 11958–11974.  https://doi.org/10.53730/ijhs.v6nS2.8231.Pellitteri, M. (2018). Kawaii Aesthetics from Japan to Europe: Theory of the Japanese “Cute” and Transcultural Adoption of Its Styles in Italian and French Comics Production and Commodified Culture Goods. Arts, 7(3), 24. https://doi.org/10.3390/arts7030024.Raman, K., Othman, A. N., Idris, M. Z., & Muniady, V. (2021). Kawaii-Style Pedagogical Agents Designs in Virtual Learning Environment: A Research Conceptual Framework. International Journal of Academic Research in Progressive Education and Development, 10(01), 154-170. https://doi.org/10.6007/IJARPED/v10-i1/8489.Raubenheimer, L. (2006). Blandness and the digital sublime in Takashi Murakami’s designs for Louis Vuitton. South African Journal of Art History, 21(2), 74–88. http://hdl.handle.net/2263/10629.Rupadha, I. K. (2016). Memahami Metode Analisis Pasangan Bibliografi (Bibliographic Coupling) dan Ko-Sitasi (Co-Citation) Serta Manfaatnya untuk Penelitian Kepustakaan. Lentera Pustaka,  2(1), 58–69. https://doi.org/10.14710/lenpust.v2i1.12358.    Sanjaya, B. & Citra, P. A. C. (2022). Fenomena Aku Setelah Pandemi Covid-19 sebagai Ide Penciptaan Karya Seni Lukis. Gorga: Jurnal Seni Rupa, 11(01), 107-113. https://doi.org/10.24114/gr.v11i1.33867.Sari, M. (2020). Penelitian Kepustakaan (Library Research) dalam Penelitian Pendidikan IPA. NATURAL SCIENCE: Jurnal Penelitian Bidang IPA dan Pendidikan IPA.  6(1). 41-53. https://ejournal.uinib.ac.id/jurnal/index.php/naturalscience/article/view/1555.Sharp, K. (2007). Superflatlands : The global cultures of Takashi Murakami and superflat art. ACCESS: Critical Perspectives on Communication, Cultural & Policy Studies, 26(1), 32–42. https://search.informit.org/doi/10.3316/informit.665904534038717.  Uzelac. G. (2022). Harnessing The Myths of Now :Restoring Social Harmony Through Mythic Art. The University of Sydney, 1-69. https://hdl.handle.net/2123/27724.Yazovskaya, O., (2018). Artistic Language of Mass Culture As Illustrated By Takashi Murakami (On Materials From “Under The Radiation Falls” Exhibit, 2017-2018, Moscow).  IJASOS-International E-Journal of Advances in Social Sciences, IV(11), 516-520. https://doi.org/10.18769/ijasos.455682.